Optimization of Learning Through Edmodo-Based Hybrid Learning to Improve Learning Independence and Learning Outcomes - Kulsum, Umi (Indonesian Journal of Educational Studies, 2020)
The study aims to determine the effectiveness of the use of Edmodo as a media study review of the learning outcomes; Knowing the learning independence relationship with learning outcomes and Knowing the influence of hybrid learning on learning independence and learning outcomes. This is experimental method with  Non-Equivalent  Control  Group Design,  consists of four groups of treatment with varied hybrid learning proportions,  each  50% (meaning  50%  learning hybrid learning and  50%  face to face), 60% (meaning  60%  of hybrid learning and  40%  face to face),  and  70% (meaning  70%  hybrid learning and  30%  face-to-face),  and one  group of others is a  conventional group (only face to face),  this group as a  control group. Data Collection with questionnaires for learning independence and knowledge tests to determine learning achievement. The  results  showed: (1)  the  use  of  Edmodo  was  effective  in  enhancing  the  results  of  a  larger  experimental  class  learning  compared  to  the  control  class  so  that  learning  became  Optimal, (2) a  significant  relationship  of learning independence learning  with  learning  outcomes,  significance  0.000, (3)  there  is  a  difference  of  influence  of  significant  variation  of  hybrid  learning  to learning independence and  learning  outcomes,  with  significance  0,037